Perlindungan Hukum Anak dalam Kandungan Hasil Zina Perspektif Hukum Positif dan Hukum Islam - Moh. Wahyu Al Waris; Ahmad Junaidi (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
This research deals with special problems in children resulting from adultery. This is shown in article 100 of the Compilation of Islamic Law (KHI) whose family relationship is only with the mother and the mother's family. The four schools of thought agree that children from adultery do not receive a lineage from their father. The formulation of the research problems are, 1) What is the role of state institutions in guaranteeing and protecting the rights of children born from adultery? 2) How is the legal protection of children's rights in the womb resulting from adultery from a positive legal perspective? 3) How is the legal protection of children's rights in the womb resulting from adultery from the perspective of Islamic law? This research is normative legal research research on secondary data from primary, secondary, and tertiary legal materials through literature review based on the Al-Quran and hadith, books, laws and regulations and other related matters. The result of this research is that the state's efforts to guarantee protection have been carried out through laws that are general in nature. However, there are no specific rules to guarantee legal protection for children in the womb of adultery. MK Decision No. 46/PUU-VII/2010 is a bright spot in legal protection for children resulting from adultery, namely having the same rights and treatment as children in general by means of proof and recognition of child status by their biological father. Meanwhile, the perspective of Islamic law also issued MUI Fatwa NO. 11 of 2012 concerning Children resulting from adultery and their treatment that children resulting from adultery do not have a family relationship with their father, and are only related to their mother and family. However, the biological father is obliged to provide the fulfillment of the child's rights with responsibility for adultery children who have existed since the womb.